Factors associated with the level of physical activities among non-academic staffs in the Faculty of Medicine and Health Sciences of a public university in Selangor, Malaysia - Leong, Whye Sook; Sablihan, Nur Izzah Aini; Ismail, Suriani; Devaraj, Navin Kumar; Ching, Siew Mooi (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: Many Malaysians does not engage in regular physical activity. The objective of this study was to deter-mine the factors associated with the level of physical activity among non-academics staff in the Faculty of Medicine and Health Sciences (FMHS), Universiti Putra Malaysia (UPM). Methods: This was a cross-sectional study using a self-administered questionnaire consisting socio-demographic, International Physical Activity Questionnaires (short form) and Depression, Anxiety and Stress Scale (DASS) scales to measure the level of physical activity and association with psychosocial and environmental factors. Ethical approval was obtained from the Ethics Committee for Research Involving Human Subjects (JKEUPM). Data was analysed using the SPSS 20.0. A p value of ≤ 0.05 was considered as statistically significant. Results: The response rate was 84% or 120 respondents. 68 (56.7%) respondents was found to have a good level of physical activity. Majority of them were women (70 [58.3%]), aged of < 33 years old (72 [60.0 %]), Malays (113 [94.2%]), and had tertiary education (81[67.5%]). There are significant associations between socio-demographic factors [gender (p=0.013), age (p=0.025) and level of education (p=0.020)] and environmental factor (performing physical activity at gymnasium (p=0.021)) with the level of physical activity on univariate analysis. On multivariate logistic regression, lower educational level (OR 2.96, p=0.016) and performing physical activity at gymnasium/sport centres (OR 4.66, p= 0.026) were associated with engaging with physical activity. Conclusion: Majority of the respondents have a good level of physical activity. Interventions should be planned for staffs otherwise identified as not having a good level of physical activity.